Spin-Polarized Tunable Photocurrents - Berdakin, Matias (2021)
Harnessing the unique features of topological materials for the development of a new generation of topological based devices is a challenge of paramount importance. Using Floquet scattering theory combined with atomistic models we study the interplay among laser illumination, spin, and topology in a two-dimensional material with spin-orbit coupling. Starting from a topological phase, we show how laser illumination can selectively disrupt the topological edge states depending on their spin. This is manifested by the generation of pure spin photocurrents and spin-polarized charge photocurrents under linearly and circularly polarized laser illumination, respectively. Our results open a path for the generation and control of spin-polarized photocurrents.